The Occasional Democratisation of Party Leadership Selection: A~Mechanism-Centred Approach - Anne Küppers (Politische Vierteljahresschrift, 2023)
Membership ballots have gained increasing popularity for party leadership selection around the globe. Still, our understanding of why parties use primaries is limited. This is due to two shortcomings of existing research: First, previous research has failed to satisfactorily operationalise subjective concepts such as electoral defeat. Second, quantitative studies cannot account for causal complexity. Thus, to uncover the puzzle of why parties use party primaries, this article pursues a~novel approach. I~offer new insights by using theory-testing process tracing to uncover the complex causal mechanisms that explain the use of membership ballots, taking Germany as an example. In the four cases studied, I~find that it is a~combination of an electoral shock, internal conflict, and instrumental motives that explain the decision to hold a~primary for party leadership selection.
Keywords: 320; Party primaries; Membership ballots; Party leaders; Process tracing; Causal mechanisms; Urwahlen; Mitgliederbefragung; Parteivorsitzende; Process-Tracing; Kausale Mechanismen